2014
DOI: 10.2224/sbp.2014.42.9.1537
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Positive Affect, Person-Job Fit, and Well-being on Job Performance

Abstract: Our aims in this study were to examine the positive affect and person-job fit of team members and the effect of their sense of well-being on their job performance. Participants were 212 employees of 10 life insurance companies in Taiwan. We developed a survey to measure employees' positive affect, person-job fit, well-being, and job performance. Results showed that the employees' positive affect had a positive effect on both their sense of well-being and job performance, there was a highly significant positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 22 publications
3
56
0
7
Order By: Relevance
“…When the employee's ability and the complexity of the job do not fit, this can lead to poor job performance. In an empirical study, Lin et al (2014) provided evidence to support the positive relationship between person-job fit and employee job performance. Therefore, two hypotheses are proposed:…”
Section: Person-job Fit and Employee Well-being And Performancementioning
confidence: 99%
“…When the employee's ability and the complexity of the job do not fit, this can lead to poor job performance. In an empirical study, Lin et al (2014) provided evidence to support the positive relationship between person-job fit and employee job performance. Therefore, two hypotheses are proposed:…”
Section: Person-job Fit and Employee Well-being And Performancementioning
confidence: 99%
“…Previous research has revealed the positive effects of person-job fit on organizational citizenship behavior and job performance and the negative impact on turnover intention (Hassan et al, 2012;Lin et al, 2014). Therefore, person-job fit is an essential goal in job searching and occupational mobility.…”
Section: Career Success Criteria Clarity and Person-job Fitmentioning
confidence: 99%
“…The notion of well-being essentially relates to a broad notion of happiness (Ryan & Deci, 2001;Waterman, 1993), and as mentioned in Lu (2001), the notion denotes an assessment of life of an individual, including life satisfaction and positive effect. There are two dimensions of well-being, namely subjective well-being (SWB) and psychological well-being (PWB) (Lin et al, 2014), where the former relates to the life evaluation made by individuals, and the latter relates to living a full life based on own prospect (e.g., transforming happiness from potential to achievement) and having the awareness concerning the nature of the outlook of human development.…”
Section: Psychological Well-being and Job Performancementioning
confidence: 99%